THE IMPACT OF MONETARY VARIABLES ON EXCHANGE RATE IN MALAYSIA FROM 2013 UNTIL 2015 - Michele Crystalina Ng; Caroline Geetha (Malaysian Journal of Business and Economics (MJBE), 2020)
This research aims to study the relationship between exchange rate and this study’s independent variables which are, inflation rate, interest rate and foreign exchange reserve in Malaysia. Secondary data from period of 2013 M1 until 2015 M12, which was retrieved from Bloomberg Data. This study uses empirical tools which is E-Views 11 to compute the variables data into empirical result. The results obtained showed that there is a positive insignificant relationship between inflation rate and exchange rate. However, for interest rate, this study found that there is a negative insignificant relationship between interest rate and exchange rate which implies that interest rate has a negative correlation with exchange rate. Further, based on the result of this study, negative relationship is obtained between foreign reserve money and exchange rate which means when there are trends of increase export and remittance will have positive effect on exchange rate while when there is a trend of increase import and foreign reserve money gave a negative impact on exchange rate. As predicted by the literature review, inflation rate and interest rate should have a negative relationship between exchange rate and foreign exchange reserve should have a positive relationship between exchange rate. Yet, this study found an inverse and slightly different compared with the pasted researches done by many researchers. As this study have its limitations, thus recommendations are suggested for researches that will be done in future.